2012
DOI: 10.1111/ger.12012
|View full text |Cite
|
Sign up to set email alerts
|

Candida colonisation and the efficacy of chlorhexidine gluconate on soft silicone‐lined dentures of diabetic and non‐diabetic patients

Abstract: Dentures with silicone resilient liner exhibit increased Candida growth in diabetic patients. Four per cent chlorhexidine gluconate solution effectively disinfects these dentures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…Regardless of the issues of surface free energy, the conventional wisdom is that higher amounts of Candida albicans are accumulated on soft relining materials than on conventional acrylics 8,9 . The results of this study, however, suggest that this assumption is only valid for prolonged incubation periods, which simulate long-term denture wearing without proper hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the issues of surface free energy, the conventional wisdom is that higher amounts of Candida albicans are accumulated on soft relining materials than on conventional acrylics 8,9 . The results of this study, however, suggest that this assumption is only valid for prolonged incubation periods, which simulate long-term denture wearing without proper hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…Of 47 clinical trials, 22 were excluded for the reasons reported in Table . Eventually, 25 CCTs met the predefined inclusion criteria in order to arrive at the final selection . These were further classified into 4 categories according to their objective of investigation; 21 CCTs (17 RCTs and 4 N‐RCTs) examined denture hygiene practices in terms of effectiveness pertaining to either killing or inactivation of microorganisms or removal of denture biofilm in individuals with no clinical signs of denture stomatitis, 3 CCTs examined denture hygiene approaches in terms of colour stability and 2 CCTs tested microwave disinfection with regard to dimensional stability .…”
Section: Resultsmentioning
confidence: 99%
“…Eventually, 25 CCTs met the predefined inclusion criteria in order to arrive at the final selection . These were further classified into 4 categories according to their objective of investigation; 21 CCTs (17 RCTs and 4 N‐RCTs) examined denture hygiene practices in terms of effectiveness pertaining to either killing or inactivation of microorganisms or removal of denture biofilm in individuals with no clinical signs of denture stomatitis, 3 CCTs examined denture hygiene approaches in terms of colour stability and 2 CCTs tested microwave disinfection with regard to dimensional stability . Finally, 30 articles investigated the attitudes and habits of removable denture wearers towards the hygiene of their prostheses, including the frequency, of the applied hygiene interventions as well as the presence of nocturnal wearing of removable dentures …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations